2010
DOI: 10.1007/s11307-010-0317-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Intravenous Toxicity Study of IRDye 800CW in Sprague-Dawley Rats

Abstract: ObjectiveFluorophore-labeled contrast imaging agents are moving toward clinical use for a number of applications. The near-infrared dye IRDye 800CW is frequently used in its N-hydroxysuccinamide (NHS) ester form for labeling these agents. Following conjugation or breakdown of a labeled ligand, excess NHS ester is converted to the carboxylate form. To prepare for clinical use as a near-infrared fluorophore, a toxicity study was conducted on IRDye 800CW carboxylate.MethodsMale and female Sprague–Dawley rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(180 citation statements)
references
References 28 publications
7
173
0
Order By: Relevance
“…IRDye 800CW is a NIR fluorophore with optimal characteristics for clinical use, allowing binding to antibodies when used in its N-hydroxysuccinimide (NHS) ester form. A preclinical toxicity study with IRDye 800CW carboxylate showed no toxicity in doses of up to 20 mg/kg intravenously or intradermally (16).…”
mentioning
confidence: 99%
“…IRDye 800CW is a NIR fluorophore with optimal characteristics for clinical use, allowing binding to antibodies when used in its N-hydroxysuccinimide (NHS) ester form. A preclinical toxicity study with IRDye 800CW carboxylate showed no toxicity in doses of up to 20 mg/kg intravenously or intradermally (16).…”
mentioning
confidence: 99%
“…A major shortcoming of ICG, however, is that it lacks a reactive functional group and therefore, cannot be used to label targeting agents. 33 Because most cancers are heterogeneous in nature and may exhibit different expression patterns, it may be that combinations of labeled tumor-targeting agents are necessary to completely visualize cancers in the surgical bed. Variations in tumor antigens, both between tumors and within a tumor, could potentially influence fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This NIR fluorescent dye underwent extensive toxicity testing and is a good-manufacturing-practice-compliant compound, registered at the U.S. Food and Drug Administration (16,17).…”
Section: Fluorescent Labeling Of Monoclonal Antibodiesmentioning
confidence: 99%